Disease progression and age as factors underlying multimorbidity in patients with COPD: results from COSYCONET - Alter, Peter; Kahnert, Kathrin; Trudzinski, Franziska; Bals, Robert; Watz, Henrik; Speicher, Tim; Söhler, Sandra; Andreas, Stefan; Welte, Tobias; Rabe, Klaus F.; Wouters, Emiel FM; Sassmann-Schweda, Antonia; et al. (The International journal of chronic obstructive pulmonary disease, 2022)
Prevalence of multimorbidity over time are attributable to COPD progression compared to increasing patient age.